The Effect of Human Pellucide Zone 3 Monoclonal Antibody on Expression of Bcl-2 and Bax in Follicle Granulosa Cells of Mice Ovary - Riny Natalina; Tatit Nurseta; Sri Winarsih (Journal of Tropical Life Science, 2018)
Pellucide zone 3 (ZP3) involves in fertilization mechanism. Moreover, antibody of ZP3 can develop to inhibit egg and sperm interaction. This study aims to determine the effect of hZP3 (mab-hZP3) monoclonal antibody on the expression of Bcl-2 and Bax in follicle granulosa cells of the mice ovary. Female mice BALB/c were divided into 12 groups which consisted of control and experimental treatment group. Each group was added with 30% of total mice as error sample (1 mice). Each groups were treated differently: 50 µl adjuvant Al(OH)3 in 50 µl Tris HCl, 20 µg Mab-hZP3, 40 µg Mab- hZP3, and 60 µg Mab-hZP3. Each group was dissected at day 10, 15 and 20. Measurement of Bcl-2 and Bax was performed with immunohistochemistry. Data was analyzed by Two-Way ANOVA. There was no significant effect of Mab-hZP3 administration in various doses on Bcl-2 (p=0.0825), and Bax (p=0.836). There was no significant effect of administration of Mab-hZP3 in time (p=0.807), neither on Bcl-2 expression (p=0.088) and Bax (p=0.227). The lowest Bcl-2 level was found in dose of 60 µg in day 15. There was no significant effect of Mab-hZP3 in various doses and time (p=0.691), neither to Bcl-2 and Bax. Such results obtained due to the specificity of a monoclonal antibody that recognizes specific antigen. Mab-hZP3 is proposed as immunocontraception for women causing no disturbance of folliculogenesis.